Effectiveness of combination use of intralesional steroid with 5-fluorouracil in the treatment of keloid patients - Arpan Kumar Basak; Joya Debnath; Hossain, Md Munjur; Hasanat, Md Abul (Mediscope, 2024)
Background: Keloids are a common problem with significant recurrence rates despite intralesional steroid treatment and 5-fluorouracil in combination with triamcinolone may be superior to triamcinolone alone. Objectives: To evaluate the effectiveness of the combination use of intralesional steroids with 5-fluorouracil in the treatment of keloid. Methods: The study was a descriptive cross-sectional study and was conducted at the Department of Dermatology and Venereology, Khwaja Yunus Ali Medical College (KYAMC), Enayetpur, Sirajganj, from July 2020 to June 2021. A total of 100 patients with keloid were included in this study. These patients were subjected to history, clinical examination, and investigations. In all cases, informed written consent was taken from the Participants and a separate case record form was used during data collection. Collected data were analyzed by the statistical software IBM SPSS 25. Results: This study shows that the majority (68%) of patients belonged to the age group of 21-30 years. The mean age was 26.43±7.77 years. Regarding sex, 56% were females and 44% were males with a male-female ratio of 1.3:1. 52% of patients had a duration of lesion up to 1 year, 22% of patients had 1-2 years and 26% of patients had >2 years. The most common site of keloid was the chest (38%), then face (32%), upper extremity (16%), shoulder (6%), back (4%). The most common presenting symptoms were pruritis (56%), then 38% were cosmetic disfigurement, 32% were skin discoloration, 28% were pain and 18% were restriction of movement. Trauma was the commonest factor seen in 34% of the patients followed by ear piercing (22%) and infection (20%). Other causes were spontaneous (10%), acne (6%), burns (6%), and post-surgical keloid (2%). 16 had a positive family history of the keloid disease. The majority (70%) had good outcomes followed by excellent outcomes in 22% and 8% had average outcomes. It was observed that most patients (88%) did not have any adverse effects. Only 12% had adverse effects seen as skin ulceration (6%), skin atrophy (4%) and telangiectasia (2%). Conclusion: This study revealed that the combination use of intralesional steroids with 5-fluorouracil in the treatment of keloid seems to offer the balanced benefit of faster and more efficacious response with fewer adverse effects. Treatment has to be individualized and can be combined with one or more modalities to aim for better efficacy and safety. Mediscope 2024;11(1): 41-47